GMCA: a greedy multilevel clustering algorithm for data gathering in wireless sensor networks. (1st January 2013) - Kumar, Manish; Verma, Shekhar; Agarwal, Neerav
Data gathering plays an important role in several applications of wireless sensor network (WSN). In an energy constrained WSN environment, the data gathering must be energy efficient to maximise the operational lifetime of the network. This paper proposes GMCA for data gathering which makes a dynamic backbone for data transfer to the base station. This results in the enhancement of the network lifetime. The approach endeavours to find the most energy efficient path for every message and distribute energy consumption evenly in the network simultaneously. Simulation results show that GMCA performs better than existing algorithms and enhances the lifetime of a sensor network significantly.